Temperature Control of a Process with Discharge Air Recirculation and Measurement Lag - Busboom, Axel (2021 26th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA ), 2021)
This paper deals with controlling a process that requires a constant air temperature at its inlet. Temperature control is achieved by partially recirculating the hot discharge flow from the process and mixing it with cooler ambient air. The system is characterized by a deadtime in the recirculation path, lagging temperature measurements at the process inlet and discharge, and by slow dynamics of the actuator influencing the recirculation fraction. As a control structure we propose a three-point controller with a deadband and hysteresis, combined with a delayed feedback. Due to the nonlinear nature of the system, the parameters of the delayed feedback are subject to scheduling, depending on the current recirculation fraction. In order to swiftly react to changes in the process load, an additional feedforward path from the process exhaust is proposed. Performance and robustness of the controller are confirmed in simulations and field experiments.